2012
DOI: 10.1159/000335870
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Ductal Carcinoma Arising from an Ectopic Pancreas in the Gastric Wall: A Long-Term Survival Case

Abstract: A case of invasive ductal carcinoma of an ectopic pancreas in the stomach in a 74-year-old woman is presented. A 4.0 cm gastric submucosal tumor (SMT) was resected surgically. Histologically, the tumor showed cystic tissue consisting of an ectopic pancreas with foci of a moderately differentiated tubular adenocarcinoma. In this tumor, small pancreatic tissues, acini, Langerhans islets, and ductular cells were detected in the gastric SMT. The patient has experienced long-term survival. The incidence of pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…If malignancy is suspected extended oncological surgical resection (e.g., PPPD) is justified. The prognosis of patients with adenocarcinoma arising from PH seems to be better compared to patients with tumors arising from the pancreas itself, probably due to earlier presentation [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…If malignancy is suspected extended oncological surgical resection (e.g., PPPD) is justified. The prognosis of patients with adenocarcinoma arising from PH seems to be better compared to patients with tumors arising from the pancreas itself, probably due to earlier presentation [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 8 cases no information about tumor markers was reported. Of the remaining 10 cases carcinoembrionic antigen and carbohydrate antigen 19-9 were elevated in 30% of cases [ 31 , 34 , 36 ] and Ca72-4 elevated only in one case. [ 7 ] Majority of the tumors were located in antropyloric region (78%) with submucosal stenotic lesion protruding into the lumen and intact mucosa (61%).…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al, [36] 2012 74, F Middle corpus Submucosal tumor Epigastralgia I Uneventful (11 yr) 2.0 × 2.0 × 2.0 Elevated Lemaire et al, [37] 2014 60, M Lesser curvature NR Dyspepsia and epigastric heaviness NR Disease-free (4 yr) 7.5 × 4.4 Elevated…”
Section: Tumour Markersmentioning
confidence: 99%
“…We performed a systemic search of the PubMed database for the English-language literature up to June 2020 using the search term ‘heterotopic pancreas’ and ‘ectopic pancreas’. Our review of the literature identified only five cases including ours published to date ( Table 1 ) [ [9] , [10] , [11] , [12] ]. The mean patient age was 75 (43–80) years; three patients were men (60%).…”
Section: Discussionmentioning
confidence: 99%